PENGARUH SDM PETERNAKAN SAPI POTONG TERHADAP PEMBANGUNAN PETERNAKAN BERKELANJUTAN - ROMADHON R.; AMAM .; S. ROMADHONA; S. RUSDIANA (Fakultas Peternakan Universitas Udayana, 2022)
Human Resources (HR) in the beef cattle sector is one of the important factors needed and has a role in the sus- tainability and success of the livestock farming business. The purpose of this study was to analyze the influence of beef cattle human resources on sustainable livestock farming business development. The research variables consist of human resources (X) and 5 (five) dimensions of sustainable livestock farming business development, namely the ecological dimension (Y1), the economical dimension (Y2), the social and cultural dimension (Y3), the institutional dimension (Y4), and technological dimension (Y5). The research was conducted in Purnama Village, Tegalampel Sub-Districts, Bondowoso District. The research was conducted using by the observation method, Focus Group Discussion (FGD), and surveys and interviews with respondents. Analysis of the data used in this study is by using a simple linear regression method with SPSS 26.0. The results showed that the ecological dimension was positively and significantly influenced by beef cattle farmers HR by 0.202, the economical dimension was positively and sig- nificantly influenced by beef cattle farmers HR by 0.194, the institutional dimension was positively and significantly influenced by beef cattle farmers HR by 0.198, and technologal is positively and significantly influenced by the cattle farmers HR of beef cattle farmers by 0.174. The conclusion of this study is that beef cattle farmers HR have an effect on the sustainable livestock farming business development, especially on the ecological dimensions, economical dimensions, institutional dimensions and technological dimensions.